RELATIONSHIP BETWEEN MARRIAGE AGE AND MOTHERS' ABILITY TO TAKE CARE OF INFANTS AGED 0-12 MONTHS AT PUSKESMAS BULANGO SELATAN - Ali, Regina Cahyani; Hafid, Ridha; Mohamad, Rini Wahyuni (Jambura Nursing Journal, 2025)
Infant care is crucial because the immature organs of infants cannot independently adapt to their surroundings. Therefore, mothers have a significant role in infant care to ensure healthy living for every infant through proper and appropriate care procedures. One factor contributing to mothers' inability to take care of their infants is their marriage age. According to the information from the KIA (Kesehatan Ibu dan Anak or Maternal and Child Health) midwife at the Puskesmas Bulango Selatan in 2024, six infant deaths (IMR) were reported involving mothers who married under the age of 20. This study adopts a correlational analytical design with a cross-sectional approach. The variables in this study consist of the independent variable, marriage age, and the dependent variable, mothers' ability to care for infants aged 0-12 months. The sampling technique employs purposive sampling, with a population of 128 respondents and a sample of 56 respondents. The instrument of study is a questionnaire, and the data analysis technique uses the Chi-Square test, resulting in a p-value of 0.000, indicating a relationship between marriage age and mothers' ability to take care of infants aged 0-12 months at the Puskesmas Bulango Selatan. In conclusion, a significant relationship exists between marriage age and mothers' ability to care for infants aged 0-12 months at the Puskesmas Bulango Selatan. Moreover, this study is expected to serve as a reference for the Puskesmas Bulango Selatan in enhancing health promotion efforts to raise awareness about the ideal age for marriage and mothers' ability to care for infants aged 0-12 months.